Design of Cu-based intermetallic nanocrystals for enhancing hydrogenation selectivity. (16th March 2019) - Yu, Hongbo; Tang, Weiqiang; Li, Kaijie; Yin, Hongfeng; Zhao, Shuangliang; Zhou, Shenghu
Graphical abstract: Highlights: New ordered nanocatalysts can selectively transform nitroaromatics into aromatic amines. mplA sie method to obtain intermetallic compounds in wet chemistry is developed. Electronic and geometric effects upon ordered structure enhance catalytic performance. Abstract: Motivated by the high performance of intermetallic compounds with their ordered structures, developing synthetic methods for preparing intermetallic compounds is highly desired. Herein, we report facile syntheses and rational design of the structurally ordered Cu-based intermetallic compounds (CuM (M = Pt, Pd, Au)). To achieve this, intermetallic nanoparticles were synthesized in solution by a butyllithium co-reduction method at 240 °C. The developed wet-chemistry syntheses of ordered intermetallic CuM nanoparticles avoided solid annealing process, and thus relatively small intermetallic nanocrystals were formed. The ordered PtCu nanocatalysts displayed enhanced chemoselectivity relative to the PtCu solid-solution alloy and individual monometallic nanocatalysts for catalytic hydrogenations of a series of substituted nitroaromatics. The DFT-based theoretical calculations for hydrogenations of halonitrobenzenes suggest that the surface geometry of ordered PtCu structures favor the hydrogenation of nitro substituent and disfavor the hydrodechlorination by-reaction, resulting in enhanced chemoselectivity.